Assessment of Genetic Variation in Apis nigrocincta (Hymenoptera: Apidae) in Sulawesi Revealed by Partial Mitochondrial Cytochrome Oxidase I Gene Sequences. (7th April 2020) - Lombogia, Christian A.; Posangi, Jimmy; Pollo, Hard N.; Tulung, Max; Tallei, Trina E.
Abstract : Asian cavity-nesting honey bee Apis nigrocincta, a native bee species from Sulawesi and the Philippines, plays a vital role in pollinating flowering plants in local ecosystem and agriculture. In this study, we assessed the intraspecific genetic variation of A. nigrocincta using the sequence of cytochrome c oxidase subunit I (COI). Molecular phylogenetic analysis showed that there were three main clades in A. nigrocincta specimens from Sulawesi based on their respective locations (North, Central, and South Sulawesi). Genetic distance analysis using the Kimura 2-parameter (K2P) model showed that the intraspecific genetic distance in Sulawesi specimens ranged from 0.000 to 0.055. There are 26 nucleotide polymorphic sites within Sulawesi A. nigrocincta . The variation was dominated by transition T ↔ C. The molecular identification result was supported by morphological identification. The results of the two methods agree that the specimen under study was A. nigrocincta . The result of genetic distance calculation indicated that although the tested specimens were derived from remote locations, the genetic variation was still within the range of intraspecific variation.